2022
DOI: 10.1177/21501319211062673
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Disordered Eating Behavior Among Adolescent Girls: Screening and Education

Abstract: Introduction/Objectives: An unhealthy relationship with food can lead to disordered eating in adolescence, highlighting the importance of screening. This study describes the frequency of disordered eating behavior among female adolescents, as well as associated characteristics and health behaviors. Methods: Data are from a multidimensional risk factor screening survey administered at a university medical center’s adolescent clinic from 2016 to 2018. The instrument was adapted from existing screening tools such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…In order to properly assess the risk-benefit balance, understanding the metabolic profile of the e-cigarette users seems like an important aspect. As mentioned, we need to look at the most important metabolic components with respect to e-cig use, from type 2 diabetes mellitus to milder glucose profile anomalies (such as prediabetes) to obesity, insulin resistance, and entire panel of metabolic syndrome [65][66][67][68][69][70][71][72][73].…”
Section: E-cig and Data With Regard To Prediabetes And Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to properly assess the risk-benefit balance, understanding the metabolic profile of the e-cigarette users seems like an important aspect. As mentioned, we need to look at the most important metabolic components with respect to e-cig use, from type 2 diabetes mellitus to milder glucose profile anomalies (such as prediabetes) to obesity, insulin resistance, and entire panel of metabolic syndrome [65][66][67][68][69][70][71][72][73].…”
Section: E-cig and Data With Regard To Prediabetes And Diabetesmentioning
confidence: 99%
“…The profile of the obese patient might favor e-cigarette use due to weight control reasons, to prevent binge eating considering nicotine's appetite suppression effects [65], and to satisfy cravings using the large flavor palette available in these products [22,23,66]. Oftentimes, e-cigarette smoking is associated with eating disorders, including not only binge eating, and bulimia nervosa, but also anorexia [67], especially in adolescent girls [68,69]. Of note, Sompa et al [18] found an association between higher BMI, waist circumference and % body fat with dual smoking only in females, but not in males [18].…”
Section: E-cig Users and Obesitymentioning
confidence: 99%